Rancang Bangun Aplikasi Administrasi Perbaikan Kendaraan Pada Vehicle Operation Management Berbasis Web di PT Altrak 1978 Samarinda - Renaldi Anwar; Fahrullah Fahrullah; Dedi Mirwansyah (LP3M Universitas Mulia, 2021)
PT ALTRAK 1978 Samarinda is a large branch that has several departments, including HR&GA, FA, Marketing, Part, Rebuild Center, Service and VOM (Vehicle Operation Management). The task of VOM is to maintain, repair and manage all operational vehicle assets owned by PT. ALTRAK 1978 at 10 Depos in the Kalimantan area, and one of the tasks of VOM is to create reports for all processes carried out at VOM and everything related to company operational vehicles, but many reports are made that require data from vehicle repairs such as operational vehicle repair history . When retrieving data from the repair history, we always experience difficulties because the data is incomplete and not integrated between several parts at PT. ALTRAK 1978 Samarinda and until now, if there are complaints about damage to operational vehicles, vehicle users still experience problems when they want to report damage to these vehicles because there is no administration system in every vehicle repair administration process. The formulation of the problem is how to make it easier for VOM to report vehicle repairs with a data source or repair history that can be seen and retrieved easily by several parties involved in the vehicle repair administration process with the aim of making it easier for VOM and vehicle users to receive and report vehicle damage quickly and in an integrated manner. each other between several departments.